2016
DOI: 10.7717/peerj.2373
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and stress in partners of Australian combat veterans and military personnel: a comparison with Australian population norms

Abstract: Partners of Australian combat veterans are at an increased risk of experiencing mental health problems. The present study provides a comparative analysis of the mental health of partners of veterans with that of the Australian normative data. To compare different types of groups of partners, the study samples comprised: (a) partners of Australian combat veterans (Sample 1: n = 282, age M = 60.79, SD = 5.05), (b) a sub-sample of partners of Australian combat veterans from the previous sample (Sample 2: n = 50; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Half of the studies reviewed (N = 12) were Australian and all focused on family members of Vietnam Veterans, specifically the relationships between Veteran PTSD and mental health outcomes in partners 53,55,56,69,72 /adult children, 57,[63][64][65][66][67]70 with the quantitative studies examining the prevalence of psychopathologies in these populations compared to other military sub-groups and national prevalence rates. Qualitative studies were very much family focused, exploring the experience of living with a Veteran's PTSD and eff ects on the entire family, both positive and negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the studies reviewed (N = 12) were Australian and all focused on family members of Vietnam Veterans, specifically the relationships between Veteran PTSD and mental health outcomes in partners 53,55,56,69,72 /adult children, 57,[63][64][65][66][67]70 with the quantitative studies examining the prevalence of psychopathologies in these populations compared to other military sub-groups and national prevalence rates. Qualitative studies were very much family focused, exploring the experience of living with a Veteran's PTSD and eff ects on the entire family, both positive and negative.…”
Section: Discussionmentioning
confidence: 99%
“…54 Several studies covered multiple psychological outcomes in Australian partner populations as compared to national prevalence rates. MacDonell, Bhullar, and Thorsteinsson (Australia) 55 examined anxiety, depression, and stress in four samples of military partners, with partners of ex-service members showing mean scores for anxiety (g = 0.79), depression (g = 0.66), and stress ( g = 0.80) far more than population norms. O'Toole et al (Australia) 56 found higher prevalence rates of 11 out of 17 psychopathologies in a partner sample, with generalized anxiety disorder associated with Veteran suicidal ideation and severe single-episode and moderate recurrent depression associated with combat-related Veteran PTSD and battle casualty, respectively.…”
Section: Partners Of Veteransmentioning
confidence: 99%
“…Living in regional and rural Australian communities profoundly impacts the ability of residents to take advantage of delivery modalities and payment methods to access mental health services 4 despite having a high need for these services. Australian research reports that the Defence family members, especially partners of those deployed, experience unique caregiving stressors, poor marital adjustment and life satisfaction and significantly higher levels of depression, stress and anxiety, when compared with population norms 5 . In addition, in the absence of required specialist support, parents may not have the knowledge, skills and confidence to adequately support their children's well‐being and build their resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Australian research reports that the Defence family members, especially partners of those deployed, experience unique caregiving stressors, poor marital adjustment and life satisfaction and significantly higher levels of depression, stress and anxiety, when compared with population norms. 5 In addition, in the absence of required specialist support, parents may not have the knowledge, skills and confidence to adequately support their children's well-being and build their resilience. Defence families, and partners of those deployed, experience stressors typically not automatically associated with civilian families.…”
Section: Introductionmentioning
confidence: 99%